2004
DOI: 10.1016/j.jcrs.2003.09.068
|View full text |Cite
|
Sign up to set email alerts
|

Anterior stromal puncture in Brown-McLean syndrome

Abstract: We describe 2 cases of Brown-McLean syndrome with corneal edema successfully treated by anterior stromal puncture (ASP). Ophthalmologic examinations showed peripheral edema and aphakia in both patients. The patients had ASP to control the severe foreign-body sensation. The procedure was effective over a long-term follow-up, suggesting that peripheral ASP may be an effective therapeutic option for patients with symptomatic Brown-McLean syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 15 publications
0
5
0
1
Order By: Relevance
“…These eyes may present with transient corneal edema but do not have permanent swelling. 2 , 12 The confocal microscopy demonstrated healthy endothelium in BMS within the affected cornea. 13 Conversely, Vote et al 9 reported endothelial pigmentation, prominent nerves, and localized basal epithelial edema in peripheral cornea, while central cornea revealed large cellular structures with prominent nuclei.…”
Section: Discussion and Review Of Literaturementioning
confidence: 94%
“…These eyes may present with transient corneal edema but do not have permanent swelling. 2 , 12 The confocal microscopy demonstrated healthy endothelium in BMS within the affected cornea. 13 Conversely, Vote et al 9 reported endothelial pigmentation, prominent nerves, and localized basal epithelial edema in peripheral cornea, while central cornea revealed large cellular structures with prominent nuclei.…”
Section: Discussion and Review Of Literaturementioning
confidence: 94%
“…However, prior reports of patients with BMS described various treatments to alleviate ocular surface discomfort including topical corticosteroids, hypertonic solutions, and/or therapeutic contact lenses [ 7 ]. Other reported options include stromal micropuncture of the peripheral cornea and annular amniotic membrane transplantation [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Because both anterior stromal micropuncture and amniotic membrane transplantation are well recognized, commonly used techniques to manage painful bullous keratopathy in eyes with limited visual potential, [4][5][6][7][9][10][11][14][15][16][17][18] the combination of the 2 procedures may well be more effective than performing only 1 or the other. A review of the literature indicates that approximately 65% to 70% of patients treated with ASP have complete relief of discomfort after the procedure, 4,5 compared with 66% to 90% of patients treated with AMT alone.…”
Section: Discussionmentioning
confidence: 99%
“…19 Also, the use of amniotic membrane avoids the donor site morbidity associated with nasal and buccal mucosal grafts. Thus, we believe that the ease with which anterior stromal micropuncture and amniotic membrane transplantation are performed, the good success rate associated with each in the management of bullous keratopathy, [4][5][6][7][9][10][11][14][15][16][17][18] and the preferable cosmetic result of amniotic membrane transplantation compared with conjunctival, nasal, and buccal mucosal graft placement over the cornea 9,11,12 make this the preferred surgical technique for …”
Section: Discussionmentioning
confidence: 99%